Mayaderm - Dixit, Mukund R., (SAGE knowledge. Cases., 2016)
This case describes the journey of a doctor from curiosity to product formulation to enterprise promotion and presents the problems faced by him in succeeding commercially. The innovator perceives the innovation to be a medical success and a commercial non-starter. The case provides an opportunity to evaluate the efforts of Dr Shah and propose a strategy for the future.